Increased stability and intracellular antioxidant activity of chlorogenic acid depend on its molecular interaction with wheat gluten hydrolysate. (30th September 2020) - He, Dong; Peng, Xue; Xing, Yi-Fan; Wang, Yi; Zeng, Wen; Su, Nan; Zhang, Chong; Lu, Dian-Nan; Xing, Xin-Hui
Graphical abstract: Highlights: WGH improve the stability of CGA during simulated gastrointestinal digestion. WGH promote the intestinal epithelial cell entry efficiency of CGA. WGH increase intracellular antioxidant activity of CGA. The increased activity of CGA depend on its interaction with WGH. The interaction was proved by fluorescence quenching and molecular dynamics simulations. Abstract: Gastrointestinal stability and cell entry efficiency affect the biological accessibility of chlorogenic acid (CGA). Here, wheat gluten hydrolysate (WGH) was proven to improve the stability of CGA during simulated gastrointestinal digestion, promote the intestinal epithelial cell entry efficiency of CGA, and increase its intracellular antioxidant activity. The interaction between WGH and CGA was studied by fluorescence quenching and molecular dynamics simulations. The thermodynamic parameters and molecular dynamics simulation analysis showed that the interaction between WGH and CGA was dependent on hydrogen bonding and hydrophobic and electrostatic interactions. Analyses of the binding sites of WGH showed that Arg12, Arg49, Lys54, and Pro74-Gln89 had strong interactions with CGA molecules. This interaction between CGA and WGH was related to both electrostatic interactions and their respective concentrations. Taken together, the stability, intestinal epithelial cell entry, and antioxidant activity of CGA can be increased by its molecular interactions with WGH.